Use of enterprise simulation to assess the impacts of remanufacturing operations - Farr, Richard; Lohse, Niels (2011)
Remanufacturing could become a cornerstone of a future sustainable society and considerable progress has been made towards finding technical solutions for the renovation of products or selected components. Not all the barriers to remanufacturing are purely technical, however; others are related to business drivers, or social factors. The problems anticipated for remanufacturing, as identified by Guide [1] include “stochastic product returns, imbalances in return and demand rates, and the unknown condition of returned products.” In order to investigate the significance of these problems, a simulation model was constructed to explore the costs and benefits of a range of different end-of-life (EOL) strategies. It suggests that environmental harm can be reduced to an extent, when a company is set up to process returned goods, but that this benefit comes at the cost of considerable complications in scheduling and logistics.